Large-Scale Operational Pyriproxyfen Autodissemination Deployment to Suppress the Immature Asian Tiger Mosquito (Diptera: Culicidae) Populations - Unlu, Isik (J Med Entomol, 2020)
Effective suppression of container-inhabiting Asian Tiger [Aedes albopictus (Skuse)] (Diptera: Culicidae) and yellow fever [Aedes aegypti (L.)] (Diptera: Culicidae) mosquitoes presents one of the most intractable problems for modern mosquito control. Traditional tools often fail to control populations of these mosquito species, and are prohibitively expensive or have negative environmental impacts. Novel approaches and tools are urgently needed for integrated container-inhabiting mosquito management programs. One of the most promising techniques is autodissemination. We present the results of a long-term large-scale study conducted in a temperate urbanized environment representing typical Ae. albopictus habitats. Three treatment sites with autodissemination stations and three nearby reference sites were monitored for eggs, immature, and adult mosquitoes over a period of 3 yr from 2014 to 2016. Elevated larval and pupal mortality of 12–19% on average was the most notable outcome in sentinel cups of the treatment sites. The number of eggs in the treatment sites was significantly reduced in 2014, but not in 2015 or 2016. Adult populations remained similar in treatment and reference sites throughout the study. The impact of autodissemination on mosquito populations was lower than reported by previous investigations. Technical and logistical problems associated with wider coverage and working in multiple urban neighborhoods contributed to reduced efficacy. Incorporating autodissemination with routine mosquito control operations and commercializing this methodology for general public use will require further research on combining this tool with other novel or conventional technologies.